2009
DOI: 10.1200/jco.2008.21.2381
|View full text |Cite
|
Sign up to set email alerts
|

Phase II, Randomized, Double-Blind, Placebo-Controlled Study of Recombinant Human Intestinal Trefoil Factor Oral Spray for Prevention of Oral Mucositis in Patients With Colorectal Cancer Who Are Receiving Fluorouracil-Based Chemotherapy

Abstract: rhITF oral spray formulation was safe and effective when used for the reduction of chemotherapy-associated OM in patients with colorectal cancer. Patients exhibited high compliance in dosing administration. Future clinical study is planned to develop this drug for use in OM management in patients with cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
0
2

Year Published

2010
2010
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(37 citation statements)
references
References 37 publications
0
35
0
2
Order By: Relevance
“…ATL-104 mouthwash reduced the duration of oral mucositis, whereas its effect on the incidence of mucositis was unclear [88]. Recombinant human intestinal trefoil factor oral spray was found to be safe and effective for the reduction of CT-induced oral mucositis in patients with colorectal cancers [89], but these limited data did not permit a guideline.…”
Section: Granulocyte Colony-stimulating Factormentioning
confidence: 99%
See 1 more Smart Citation
“…ATL-104 mouthwash reduced the duration of oral mucositis, whereas its effect on the incidence of mucositis was unclear [88]. Recombinant human intestinal trefoil factor oral spray was found to be safe and effective for the reduction of CT-induced oral mucositis in patients with colorectal cancers [89], but these limited data did not permit a guideline.…”
Section: Granulocyte Colony-stimulating Factormentioning
confidence: 99%
“…TFF peptides protect mucosal cells from injury as well as contribute to epithelial reconstitution and should be considered as promising anti-mucositis agents [89]. A preclinical study suggested that a mouth rinse with genetically modified bacteria engineered to secrete human TFF-1 may provide future management tools [94].…”
Section: Recommendations For Future Researchmentioning
confidence: 99%
“…Evidence has shown that TFF3 can act on the epidermal growth factor receptor (EGFR), which then activates several downstream signaling pathways, including mitogen-activated protein kinases and the phosphatidylinositol 3-kinase (PI3K)/AKT pathway (Baus-Loncar and Giraud, 2005). TFF3 stimulated epithelial migration by phosphorylating EGFRs and then activating downstream pathways (Peterson et al, 2009). The previous studies of TFF3 have focused on its maintenance of mucosal integrity and the promotion of repair.…”
Section: Introductionmentioning
confidence: 99%
“…Evidence suggests that TFF3 serves as an initiator of mucosal healing to enable the acute restoration of cellular continuity, and TFF3-deficient mice showed an impaired capacity for mucosal recovery after colonic injury even after exposure to antineoplastic agents and total body radiation (Beck et al, 2004;Mashimo et al, 1996). Additionally, a recent clinical report showed that a recombinant human TFF3 (rhTFF3) oral spray formulation was safe and effective for the treatment of chemotherapyassociated oral mucositis in patients with colorectal cancer (Peterson et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…TFF3 increases migration of oral epithelial cells [12]. TFF3 can serve as a potential tool for the prevention and healing of mucosal ulcerations [27,28]. Considering these results, TFF3 may enhance oral mucosal repair mechanisms and may have future therapeutic implications for the treatment of patients with oral ulcerations.…”
Section: Discussionmentioning
confidence: 99%